1985
DOI: 10.1021/bi00343a040
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit skeletal myosin heads in solution, as observed by ultracentrifugation and freeze-fracture electron microscopy: dimerization and maximum chord

Abstract: The use of analytical ultracentrifugation and freeze-fracture electron microscopy in solution allowed us to observe the monomeric and dimeric forms of Mg.71. This subfragment of the myosin molecule contains the LC2 light chain and is comparable to a "native" myosin head. Sedimentation-diffusion equilibrium ultracentrifugation shows that it is necessary to use slightly different conditions in order to obtain a pure Mg.S1 dimer, as compared to the case of chymotryptic S1 (LC2-free S1). For example, in a buffer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…the isolated myosin heads can form dimers (2,10,11,17)]. We verified that the myosin was extremely pure: the index of polydispersity of our samples was typically close to zero [0.05 ( 0.05 (( SD; n ) 10)], which confirms that the head-head dimer was pure, at least for c > 0.72 mg/mL.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…the isolated myosin heads can form dimers (2,10,11,17)]. We verified that the myosin was extremely pure: the index of polydispersity of our samples was typically close to zero [0.05 ( 0.05 (( SD; n ) 10)], which confirms that the head-head dimer was pure, at least for c > 0.72 mg/mL.…”
Section: Resultssupporting
confidence: 68%
“…Studies of the possible states of aggregation of myosin and its heads (LC2-free S1 1 or Mg‚S1, which contains LC2) report contradictory findings (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Among the different data we must cite Winkelman et al (14), who found that the crystallographic unit in S1 crystals is a S1 dimer.…”
mentioning
confidence: 98%
“…It remains to be determined why the sedimentation velocity of SF, is affected significantly by changes in buffer conditions. How-2 While this report was in preparation, new evidence for dimer", formed from papain SF, was published (Bachouchi et al, 1985). Electron micrographs of SF, prepared by a freeze-fracture technique were presented, showing structures identified as dimer^.…”
Section: Discussionmentioning
confidence: 98%
“…Morel and Garrigos (1,2) found that crude LC2-free S1 (called below S1) can form dimers in solution. Bachouchi et al (3) directly visualized, by electron microscopy, myosin head dimers of LC2-free S1 1 and Mg.S1 (containing LC2). The existence of the dimeric state of S1 was not accepted for 12-13 years.…”
mentioning
confidence: 99%
“…Despite these results, the existence of dimers has been challenged by Munson et al (7) and Stafford III and Margossian (8). These authors probably overlooked the fact that the crystallographic unit in S1 crystals is a dimer (9), or considered that direct observation of the dimer by the techniques described by Bachouchi et al (3) and Winkelmann et al (9) may induce artifactual distortions, not occurring with hydrodynamic techniques. Furthermore, they could argue that the S1 routinely prepared in our laboratory was not sufficiently purified.…”
mentioning
confidence: 99%